THE EFFECT OF MARKETING DUALITY ON PERFORMANCE: USING A RESPONSE SURFACE APPROACH TO OVERCOME EMPIRICAL BARRIERS - Zaenal Aripin; Wawan Ichwanudin; Ijang Faisal (Organisasi Kreatif Indonesia Emas, 2024)
Marketing plays a crucial role in improving company performance. However, the relationship between marketing strategy and company performance is not always linear. The phenomenon known as the marketing duality effect shows the complexity in the interactions between marketing variables and company performance. To overcome the empirical obstacles associated with understanding duality effects, the response surface approach has been proposed as an effective analytical tool. This research aims to investigate the effects of marketing duality on firm performance and uses a response surface approach to overcome the related empirical obstacles. This study uses a qualitative descriptive analysis method to explore understanding of the effects of marketing duality and a quantitative response surface analysis method to model the relationship between marketing variables and company performance. The analysis shows that the duality effect of marketing has a significant impact on company performance, with interactions between marketing variables being complex and not always linear. By using a response surface approach, we can identify complex patterns in the relationships between marketing variables and company performance, and design more adaptive and responsive marketing strategies.